Recentni pobočni procesi v Zgornjem Posočju - Komac, Blaž (Geografski obzornik, 2002)
The Upper Soča valley is one of the most threatened parts of Slovenia regarding rock-falls, slides and flows. In this article some main characteristics and consequences of rock-falls triggered by the earthquake of 12th April 1998 are presented as well as those of the debris flow in Log pod Mangartom, November 2000, triggered by intensive precipitation.
Keywords: geomorfologija; plazovi; Slovenija; zemeljski plazovi; Zgornje Posočje